Feathers: Environmental implication and use in the agriculture industry - Florida Rofner, Nelino (2019)
Chicken feathers (Gallus domesticus) are as byproducts of processing plants and the lack of oversight and regulation in countries like Peru, cause that these wastes end up in water bodies or informal dumpsites, becoming environmental pollutants. However, their use in the agricultural industry promises to give better treatment to the residue, as a protein source in diet formulation mainly pigs, poultry and cattle, due to its high content of protein, amino acids, minerals and natural fibers and incorporation in the production of biofertilizer significantly improve the content of organic matter and nitrogen and positively influence soil properties and crop yield. In addition, it has great potential in the cosmetic industry, biomedical, textile, bioenergy, among other applications. Therefore, the review will address the progress related to its environmental effects and its potential in the livestock and agricultural industries, as alternatives to the treatment of these residues and minimize their environmental effects.